Neutrophil-to-lymphocyte and fibrinogen-to-albumin ratios may be indicators of worse outcomes in ICU patients with COVID-19 - Atlas, Ahmet; Altay, Nuray; Karahan, Mahmut Alp; Pehlivan, Veli Fahri; Pehlivan, Başak; Duran, Erdoğan; Erol, Mehmet Kenan (Journal of Surgery and Medicine, 2021)
Background/Aim: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in a pandemic. Early diagnosis of complications and mortality caused by this disease will guide the treatment process in patients with COVID-19. We aimed to investigate whether the neutrophil/lymphocyte and fibrinogen/albumin ratios can predict mortality in COVID-19 patients. Methods: A total of 102 adult patients (≥18 years) who were followed up in the intensive care unit (ICU) between May and August 2020 because of COVID-19 were included in this retrospective cohort study. Demographic data, comorbid diseases, and hematological parameters of the patients during admission to the ICU were examined. Hematological parameters such as leukocyte, neutrophil, lymphocyte, platelet counts, C-reactive protein (CRP), D-dimer, and lactate data were recorded. The neutrophil-to-lymphocyte ratio (NLR) and fibrinogen-to-albumin ratio (FAR) were calculated, and their effects on mortality were examined. Results: Of the patients, 71 (69.6%) were male and the mean age of all patients was 69.1 (14.3) (24–103) years. Comorbid diseases of the patients were as follows: Hypertension (n=40, 39.2%), diabetes mellitus (n=28, 27.4%), chronic obstructive pulmonary disease (n=20, 19.6%), coronary artery disease (n=14, 13.7%), heart failure (n=4, 3.9%), and cerebrovascular disease (n=3, 2.9%). Mortality was higher in older patients (median age = 72; range = 62–80 years) (P=0.043), and bilateral infiltration was observed in lung computed tomography images of all patients who died. Mortality was higher in patients with NLR>9.16, FAR>0.15, D-dimer>2.01 mg/L, CRP >11.6 mg/dL, lactate >2.3 mmol/L. Conclusion: Elevated levels of neutrophil-to-lymphocyte Ratio, fibrinogen-to-albumin ratio, D-dimer, CRP, and lactate were associated with worse outcomes among COVID-19 patients in the ICU.